Pengembangan Keprofesian Berkelanjutan: sebagai Upaya Meningkatkan Teacher Profesionality - Sari, Prima Rosita; Ichsanti, Dahlia Fitri; Alwatasi, Umar; Astuti, Ramadhani Tri; Husna, Difa’ul (MASALIQ, 2023)
This article aims to determine continuous professional development for teachers. This research includes using the library research model. In this study analyzes related to sustainable professional development. This study uses a library research model with data collection in the form of a literature review. Retrieval of sources is done by looking for scientific journals in journal articles concerning the title and theme of this study. This continuous professional development is the development of teacher competencies which is carried out as needed, in stages, continuously to improve their professionalism. Continuous professional development programs are related to the existence of a profession as a teacher, in which continuous professional development is expected to improve pedagogical, professional, social and personality competencies to achieve all future demands. So that teachers are required to be able to follow and understand changes such as policies in educational institutions, an increasingly developing curriculum, learning systems that keep up with the times, and developments in science.